17β-estradiol potentiates TREK1 channel activity through G protein-coupled estrogen receptor. Issue 183 (October 2018) - Choudhury, Nasreen; Sikdar, Sujit Kumar
Graphical abstract: Highlights: 17β-Estradiol acutely increases hTREK1 channel activity through hGPER. The potentiation is pertussis toxin-sensitive involving the action of Gβγ subunits. The effect involves cAMP-PKA pathway downregulation and action of phosphatases. Serines 315 and 348 in hTREK1 carboxy terminal are targeted for dephosphorylation. Abstract: TWIK-related potassium channel 1 (TREK1), a two-pore domain potassium channel, is modulated by various hormones and neurotransmitters by activation of membrane receptor - coupled second messengers. 17β-estradiol is a neuromodulator capable of regulating several cellular processes including the activity of ion channels, in a rapid and non-genomic manner. The G protein-coupled estrogen receptor (GPER) is known to facilitate rapid actions of 17β-estradiol, though its role in modulation of ion channels is not widely explored. Several studies have shown both TREK1 and 17β-estradiol to be neuromodulatory but the interaction between them is not known. In the present study, using single channel cell-attached patch clamp electrophysiology in HEK293 cells, we show that 17β-estradiol increases the activity of hTREK1 channel by acting through hGPER and increasing the channel opening probability within minutes. The potentiation induced by 17β-estradiol is pertussis toxin – sensitive involving action of Gβγ subunits while the inhibitory effect of cAMP-PKA pathway on TREK1 is reduced. Protein phosphatases were also found to be important for the action of 17β-estradiol, which in concert with reduced activity of PKA, may alter the phosphorylation state of the channel and thus increase channel activity. Mutational studies revealed the serines at positions 315 and 348 in the C-terminal domain of hTREK1 to be the target sites for dephosphorylation induced by 17β-estradiol action through hGPER. Elucidation of the pathway for the potentiating action of 17β-estradiol via hGPER on hTREK1 channel activity will help us understand better one of the many possible neuroprotective mechanisms of 17β-estradiol and hTREK1 channel.